REKA CIPTA PERHIASAN TARI SRIMPI PAKU ALAM IV YOGYAKARTA - Yulriawan Dafri (Corak : Jurnal Seni Kriya, 2014)
One of the valuable heritages preserved until today within Pakualaman is the art andculture. One of the various arts and cultural heritages is Srimpi dance. There are somefundamental things on why the research / creation of Srimpi dance becomes interesting to do,besides having the purpose to reveal the existence of Srimpi dance with all the accompanyingattributes, including various attributes of jewelry through the study of visual data of WedanaRenggan in the manuscript source of Langen Wibawa. The forms of jewelry that are used in theSrimpi dance during the Paku Alam IV is also expected to be clearly visualized, so thatultimately the existence of jewelry as a complementary attribute in the Srimpi danceperformances will enrich arts and culture in strengthening the national identity in the eyes ofthe international world.Through a review of this manuscript, ten sets of jewelry with deferent designs of Srimpidance especially during Paku Alam IV have been created. Thus, other forms of creative andinnovative jewelry designs and products based on the philosophy prevailing in the Pakualamanenvironment are created.At least there are two approaches used in this research / creation, namely theapproach to art history and aesthetics. In addition, semiotic analysis is also included.Exploration and experimental methods are used when making the design process. The analysiscarried out does not look at the process of cause and effect, but more emphasizes on how tovisually express the forms of jewelry that wants to be created. Therefore, this study uses amultidisciplinary approach. Keywords: Langen Wibawa, Wedana Renggan, Jewelry, Srimpi Dance, Paku Alam IV.  Salah satu warisan berharga yang terdapat di lingkungan Pakualaman dan masih terusdilestarikan sampai saat ini adalah seni dan budayanya. Dari berbagai peninggalan seni danbudaya tersebut, salah satunya adalah tari Srimpi. Ada beberapa hal yang mendasar kenapapenelitian/penciptaan tari Srimpi menarik untuk dilakukan, selain memiliki tujuan untukmengungkapkan keberadaan tari Srimpi dengan segala atribut yang menyertainya, termasukberbagai atribut perhiasan melalui kajian data visual Wedana Renggan dalam sumber naskahkuno Langen Wibawa. Diharapkan juga akan dapat divisualisasikan secara jelas bentukbentukperhiasan yang digunakan dalam tarian Srimpi pada masa Paku Alam IV, sehingga padaakhirnya keberadaan perhiasan sebagai atribut pelengkap dalam pertunjukan tari Srimpi iniakan memperkaya khasanah seni dan budaya dalam memperkuat jati diri bangsa dimatainternasional. Melalui kajian naskah kuno ini telah diciptakan 10 set perhiasan tari Srimpi dengandesain yang berbeda khususnya pada masa Paku Alam IV, dengan demikian terciptalah bentukbentukdesain dan penciptaan perhiasan yang kreatif dan inovatif berdasarkan filosofi dan‘pakem’ yang berlaku di lingkungan Pakualaman.Sedikitnya ada dua pendekatan yang digunakan dalam penelitian ini, yaknipendekatan sejarah seni dan estetika, selain itu disertakan pula analisis semiotika. Metodepenciptaan eksplorasi dan eksperimen digunakan ketika proses pembuatan desain dilakukan.Analisis yang dilakukan tidak melihat pada proses sebab akibat, tetapi lebih ditekankan padabagaimana mengungkapkan secara visual bentuk-bentuk perhiasan yang ingin diciptakan. Olehkarena itu penelitian ini menggunakan pendekatan multidisiplin. Kata Kunci: Langen Wibawa, Wedana Renggan, Perhiasan, Tari Srimpi, dan Paku Alam IV.